LBJ's 1968 : power, politics, and the presidency in America's year of upheaval - Longley, Kyle (Cambridge University Press, 2018)
1968 was an unprecedented year in terms of upheaval on numerous scales: political, military, economic, social, cultural. In the United States, perhaps no one was more undone by the events of 1968 than President Lyndon Baines Johnson. Kyle Longley leads his readers on a behind-the-scenes tour of what Johnson characterized as the 'year of a continuous nightmare'. Longley explores how LBJ perceived the most significant events of 1968, including the Vietnam War, the assassinations of Martin Luther King, Jr and Robert Kennedy, and the violent Democratic National Convention in Chicago. His responses to the crises were sometimes effective but often tragic, and LBJ's refusal to seek re-election underscores his recognition of the challenges facing the country in 1968. As much a biography of a single year as it is of LBJ, LBJ's 1968 vividly captures the tumult that dominated the headlines on a local and global level.